THE IMPORTANCE OF MACRO- AND MICRONUTRIENTS IN DIETARY INTAKE FOR THE GROWTH AND DEVELOPMENT OF CHILDREN (BASED ON 5 PRESCHOOL EDUCATION ORGANIZATIONS IN TASHKENT CITY) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Relevance. The healthy growth and development of children are directly dependent on balanced nutrition. Deficiencies in macronutrients (proteins, fats, and carbohydrates) and micronutrients (iron, calcium, iodine, zinc, and vitamins) have been extensively studied and confirmed by international researchers as primary causes of delays in physical and mental development. However, the prevalence of these deficiencies and their specific impact on the health of children attending preschool education organizations (PEO) in Tashkent remain insufficiently studied.